Fiscal Policy and the Monetary Transmission Mechanism - Nicolas Caramp (University of California, Department of Economics, 2020)
I study the role of fiscal policy in the monetary transmission mechanism. I present a novel decomposition of the equilibrium that links the wealth effect, i.e. the revaluation of households' financial and human wealth, to the fiscal response to monetary policy. When monetary policy has fiscal consequences, monetary variables affect the timing of aggregate output, while fiscal variables determine its present value and the wealth effect. The general equilibrium dynamics of inflation can significantly amplify the impact of the wealth effect on initial output and inflation, even in a representative agent model. The analysis identifies the slope of the Phillips curve as a crucial determinant of the importance of fiscal policy and monetary-fiscal coordination for the effectiveness of monetary policy.
Keywords: E21; E52; E63; 330; Monetary Policy; Fiscal Policy; Multiple equilibria; Fiscal Theory